2020
DOI: 10.3390/vision4030033
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Motion Perception: Comparing Speed and Speed Change Discrimination for Looming Stimuli

Abstract: Judging the speed of objects moving in three dimensions is important in our everyday lives because we interact with objects in a three-dimensional world. However, speed perception has been seldom studied for motion in depth, particularly when using monocular cues such as looming. Here, we compared speed discrimination, and speed change discrimination, for looming stimuli, in order to better understand what visual information is used for these tasks. For the speed discrimination task, we manipulated the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The good precision of duration discrimination that we found depended presumably on the opportunistic use of multiple cues 40 , 41 . In theory, our participants could respond by using estimates of the initial distance of the target, height of the parabola vertex, and/or target speed, in addition to the estimate of motion duration.…”
Section: Discussionmentioning
confidence: 65%
“…The good precision of duration discrimination that we found depended presumably on the opportunistic use of multiple cues 40 , 41 . In theory, our participants could respond by using estimates of the initial distance of the target, height of the parabola vertex, and/or target speed, in addition to the estimate of motion duration.…”
Section: Discussionmentioning
confidence: 65%
“…These observations are not identical to our results. Lee and colleagues (2020) have also demonstrated that the speed change in looming stimuli is not used for speed change discrimination [19]. Therefore, in this study, the looming cue is not necessarily imperative for visual target speed perception.…”
Section: Plos Onementioning
confidence: 73%